Feeding behaviour adjustments by ewes foraging in highly heterogeneous and temporally variable environments - Agreil C.; Meuret M. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The European agri-environmental policy is encouraging livestock farmers to adopt grazing practices that contribute to biodiversity conservation. But there is a serious lack of knowledge, and a better understanding of feeding behaviour adjustments in response to diversity is needed. In order to address this question, we conducted two on-farm experiments with flocks of dry ewes foraging broom shrublands. A direct in situ observation method was used, with continuous observation of ingestive bites taken by a continuously monitored individual per experiment. A bite coding-grid enabled us to distinguish the extreme diversity of bites masses and structure. Flock activities were also scan-sampled, in order to check the consistency of individuals' behaviour with those of their flocks. Daily dry matter intakes (DMI) were high in both experiments: 77.9±10.2 and 75.1±16.9 g DMI/kg LW0.75, which is twice higher than predictions from existing models on sheep intake. Our data enabled us to explore the relationship between the quantitative daily intakes and the diversity of instantaneous feeding behaviour. Daily averages of ingestive behaviour hide the extremely large range of instantaneous values (from 0.04 to 1.2 g DM for bite mass). When vegetation size and structure declined as a result of grazing, the ewes progressively took larger bite masses with equivalent nutritive quality, thus adopting a pattern of consumption that is not consistent with the general assumption that such bites are chosen during the first days, as a result of the quantity-quality trade-off. This research provides knowledge about which type of diversity in plant parts offers a small ruminant satisfying behavioural leeway in composing its meals and reaching satiety.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)